2021
DOI: 10.1002/mar.21501
|View full text |Cite
|
Sign up to set email alerts
|

“We think you may like this”: An investigation of electronic commerce personalization for privacy‐conscious consumers

Abstract: In this study, we examine and propose a personalization technology acceptance model (TAM) for e‐commerce. We conducted a 2 (Privacy concerns priming vs. Control condition) × 2 (Personalization vs. Nonpersonalization) factorial, between‐subjects experiment among college students (Study 1, N = 205) and adult samples (Study 2, N = 211). The findings indicate consumers' perceived usefulness of personalization technology is positively related to their behavioral intentions to use an e‐commerce mobile app, supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 62 publications
(141 reference statements)
0
18
0
Order By: Relevance
“…In recent years, the continuous progress of network technology has greatly promoted the development of e-commerce industry. The application of data encryption technology in this field can better meet the development needs of ecommerce [10]. The emergence of e-commerce has greatly changed people's production, life, and social production mode.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, the continuous progress of network technology has greatly promoted the development of e-commerce industry. The application of data encryption technology in this field can better meet the development needs of ecommerce [10]. The emergence of e-commerce has greatly changed people's production, life, and social production mode.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As social exchange theory proposes (Blau, 1964), disclosing personal information to get personalized recommendations represents a social exchange, and marketing exchanges represent an estimated 70% of the economic impact of the data‐driven economy (Deighton & Johnson, 2013). Yet these benefits are constrained by privacy concerns (Bright et al, 2021; Maseeh et al, 2021; Song et al, 2021), and consumers are skeptical about the benefits they receive in exchange for their personal profile data. These challenges create a personalization–privacy paradox (Awad & Krishnan, 2006; Cloarec, 2020; Sutanto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as multiple researchers contend (Maseeh et al, 2021;Song et al, 2021), most studies on consumer privacy are cross-sectional,…”
Section: Study Designs and Contextsmentioning
confidence: 99%
“…Yet, the original formulation of the TAM model does not fully incorporate the growing privacy concerns stemming from the adoption of digital technologies into its conceptual structure. Thus, Song et al (2021) incorporate privacy concerns into the TAM model, showing that consumers' privacy concerns and willingness to self‐disclose significantly moderate the personalization‐intention relationship. Specifically, they found that the usefulness and the accuracy of personalized recommendations on e‐commerce websites are insufficient to drive “consumers” behavioral intention as long as “consumers” privacy concerns and self‐disclosure preferences are not fully addressed.…”
Section: Privacy and Retailingmentioning
confidence: 99%
See 1 more Smart Citation